Handbook of odors in plastic materials - Wypych, George (ChemTec, 2013)
Several reasons are behind formation of odors in materials, including the following: Use of other materials than polymer, especially materials required in processingUse of various process parameters and their severity in degradation of components of formulationRecycling of polymeric materials Contact with natural products (food, cosmetics, etc.) Storage Migration-evaporation Storage in the same space. Diffusion-related properties. The above reasons are analyzed for different materials to find out the best methods to prevent odor formation. The book also contains information on testing of odor changes, relationship between odor and toxicity, and the selection of raw materials for fog-free products.